Characteristics and innovative points of clinical trials of radiotherapy combined with immune checkpoint inhibitors in NSCLC over the past decade - Li, Mengting; Ding, Peng (Frontiers in Medicine, 2025)
BackgroundThis study aims to statistically and qualitatively evaluate the characteristics of immunoradiotherapy (iRT) clinical trials for non-small cell lung cancer (NSCLC) registered on the ClinicalTrials.gov website over the past decade, to help researchers grasp current research trends and design higher-quality iRT clinical trials in the future.MethodsWe conducted a cross-sectional, descriptive study of interventional non-small cell lung cancer iRT clinical trials registered from 2014 to 2024. This study focuses on the combination of different radiotherapy methods with immune checkpoint inhibitors (ICIs), minimizing attention to new immunotherapeutic drugs. It emphasizes the exploration of radiotherapy and suitable patient populations. Therefore, the types of ICIs are limited to PD-1/PD-L1 and CTLA-4 inhibitors, and the main innovative points of the included clinical trials were categorized and statistically analyzed.ResultsAs of 24 June 2024, 196 clinical trials were available for analysis. Among these trials, more than 76% of clinical trials focused on patients with stage III and higher NSCLC. About 35.2% of the studies were still recruiting, only 14.8% were marked as completed, and 12.8% had failed, with slow enrollment, safety, and funding issues being the main reasons for failure. Phase 2 trials (56.1%) led significantly, with only 11.7% of trials reaching phase 3; hence, 55.6% had a sample size of fewer than 50 participants. Nearly half (45.4%) of the studies were multi-center trials, and 54.6% had data monitoring. Durvalumab was explicitly mentioned in 30.1% of the studies. Most clinical trials (64.3%) focused on innovating radiotherapy dose adjustments, with 104 studies adopting a hypofractionated radiotherapy-based protocol.ConclusionThe number of iRT clinical trials in the NSCLC field is rapidly increasing. Most patients are in locally advanced stages or higher, with phase 2 trials predominating. Durvalumab is the representative drug, and researchers are particularly interested in optimizing radiotherapy doses, with a tendency to adopt hypofractionated radiotherapy.